An exponential approach for the system of nonlinear delay integro-differential equations describing biological species living together. Issue 3 (April 2016) - Yüzbaşı, Şuayip; Sezer, Mehmet
Abstract In this paper, we consider a system of nonlinear delay integro-differential equations with convolution kernels, which arises in biology. This problem characterizes the population dynamics for two separate species. We present an exponential approach based on exponential polynomials for solving this system. This technique reduces the model problem to a matrix equation, which corresponds to a system of nonlinear algebraic equations. Also, illustrative examples related to biological species living together are given to demonstrate the validity and applicability of technique. The comparisons are made with the existing results.